State Of Research Of Certain Aspects Of Female Criminality In Ukraine - Alina, Havlovska; Andriy, Dzyurbel (Національний науковий центр «Інститут судових експертиз ім. Засл. проф. М.С. Бокаріуса», 2023)
Research paper is devoted to the analysis of research on certain aspects of female crime in Ukraine. The article focuses on spectrum systematization of theoretical and practical issues in the field of female crime presented by scientists. The results of relevant scientific research were analyzed by examining the texts of dissertation abstracts, monographs, scientific articles, dissertations and other research papers. The main attention is paid to analysis of research papers of Ukrainian scientists in recent years. The article systematizes according to research areas (criminallegal characteristics of crimes committed by women; criminological characteristics of female criminals and female crime; criminal and executive aspects of serving a criminal sentence by convicted women) and groups of problematic issues in this field (criminal law characteristics of certain types criminal offenses committed by women, criminal and legal correction of convicted women, criminal-legal and criminological characteristics of female crime, prevention and countermeasures against female crime, etc.).
Female crime is a set of criminal offenses committed by women and is characterized by certain gender characteristics based on relevant social and biological factors, in particular, such as a woman’s place in society, a limited circle of external relations, type of response to criminogenic manifestations, victimization of behavior, etc. Female crime is characterized by such features as stability of quantitative and qualitative indicators, structural uniformity, lower level of vandalism, aggressiveness and cruelty, a lower level compared to male crime, etc. Level and structure of female crime, along with other types of crime are indicators of the society state, indicators of its spiritual development and observance of universal values. Taking into account the above, it is considered an actual study of the state of research on the issues of women’s criminal responsibility at the scientific-theoretical and applied level.
Keywords: female crime; research state